Case report: optical biopsy in HPV6 lesion - Corti, Maria Agustina (2018)
The optical biopsy is a noninvasive diagnostic procedure that performs an analysis of the tissue with an optical system that allows reaching a result without extracting the sample (excisional biopsy) from the body tissue. Particularly, we are making spectrofluorometry (SFM) observations in loci lesions and healthy surrounding areas. The tissue is accessed through the body surface, including the analysis of the skin itself or mucosal surface, or by endoscope into any cavity. We have found spectral similarities in the detection of infectious diseases of their natural spectral fluorescence. Specifically, in the analyzed cases of DNA-HPV+ patients, we observed in all of their fluorescence spectra the same type of relevant peaks. So, we present here the SFM observation of HPV6 infected hard palate case. In addition, we show in this case the positive reaction images after the topication with 3-5% acetic acid as it occurs in the cervix uterine lesion.